RISK ANALYSIS IN JAKARTA’S WASTE COOKING OIL TO BIODIESEL GREEN SUPPLY CHAIN USING GROUP AHP APPROACH - Raden Jachryandestama; Prismita Nursetyowati; Sirin Fairus; Bani Pamungkas (SINERGI, 2021)
The Jakarta regulation for waste cooking oil (WCO) shows the desired WCO to Biodiesel supply chain through the DKI Jakarta Governor Regulation Number 167 the Year 2016. Still, the implementation of said regulation proved inefficient. The study aims to analyze the risks in the supply chain because the WCO to Biodiesel supply chain is vulnerable to different risks than the typical supply chain and the green supply chain. The method used in this research is the group analytical hierarchy process (G-AHP) approach to create a consensus model between actors of the supply chain. Deep interviews were conducted with six experts to identify the risks and the normal scale was used to quantify their preference. Then, the PriEst software assisted the risk weight calculation, AHP matrix validation, and consensus modelling. The findings show the supply chain is vulnerable to 23 risks, categorized into six risk categories. The three risks that cause the most uncertainties in the supply chain are supply chain design risk, key supplier risk, and financial source risk. Technology risks and asset failure risks are the least concern because most WCO conversion is not done in Indonesia. These findings would be useful for the government to focus its effort on the most critical risks.